A Compact Difference Scheme for Solving Fractional Neutral Parabolic Differential Equation with Proportional Delay. (18th October 2017) - Gu, Wei; Zhou, Yanli; Ge, Xiangyu
Abstract : A linearized compact finite difference scheme is constructed for solving the fractional neutral parabolic differential equation with proportional delay. By the energy method, the unconditional stability of the scheme is proved, and the convergence order of the scheme is proved to be O ( τ 2 - α + h 4 ) . A numerical test is also conducted to validate the accuracy and efficiency of the numerical algorithm.